Aesthetic Experience Explained by the Affect-Space Framework - Schubert, E.; North, Adrian; Hargreaves, D. (Ohio State University * School of Music, 2016)
A framework for organizing the semantic structure of aesthetic experience is proposed. The new framework is presented in an 'affect-space' and consists of three sets of dichotomous classifications: (1) internal locus (the felt experience) versus external locus (the description of the object), (2) 'affect-valence' — the attraction to (positive valence, e.g. preference, awe) or repulsion from (negative valence, e.g. hatred, disgust) the artwork/object — versus 'emotion-valence' — the character/contemplation of an emotion (happiness-an example of positive valence, sadness-an example of negative valence), and (3) deep versus shallow hedonic tone—e.g. 'awe' is deep, 'preference' is shallow. Deep hedonic tone is proposed as a better index of aesthetic experience (awe, being moved etc.) than shallow hedonic tone (preference, pleasure, enjoyment). Deep, internal locus, affect-valence during the contemplation of an object amenable to an aesthetic judgement (beautiful, ugly etc.) presents the necessary and sufficient conditions for an aesthetic experience. The framework allows future researchers to consider which aspects of an experience come closest to actual aesthetic experience from an empirical aesthetics perspective. It also highlights the limited value in grouping together so many aesthetic experiences under the rubric of emotion, such as aesthetic emotions, preference, basic emotions and so forth. Our framework paves the way for testing and further development of theory on aesthetic experience.